2013
DOI: 10.1371/journal.pone.0068014
|View full text |Cite
|
Sign up to set email alerts
|

The Proline-Rich Motif of the proDer p 3 Allergen Propeptide Is Crucial for Protease-Protease Interaction

Abstract: The majority of proteases are synthesized in an inactive form, termed zymogen, which consists of a propeptide and a protease domain. The propeptide is commonly involved in the correct folding and specific inhibition of the enzyme. The propeptide of the house dust mite allergen Der p 3, NPILPASPNAT, contains a proline-rich motif (PRM), which is unusual for a trypsin-like protease. By truncating the propeptide or replacing one or all of the prolines in the non-glycosylated zymogen with alanine(s), we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…1a). 1b) [33]. The intrinsic fluorescence and far UV-CD analysis showed that rDer p 3 and its inactive counterpart rDer p 3-S196A exhibit a similar tertiary and secondary structure content, respectively (Figs 1b and c).…”
Section: Characteristics Of Allergensmentioning
confidence: 84%
See 4 more Smart Citations
“…1a). 1b) [33]. The intrinsic fluorescence and far UV-CD analysis showed that rDer p 3 and its inactive counterpart rDer p 3-S196A exhibit a similar tertiary and secondary structure content, respectively (Figs 1b and c).…”
Section: Characteristics Of Allergensmentioning
confidence: 84%
“…Such tion of trypsin [33]. Therefore, in the context of immunotherapy with HDM extracts, it would be of interest to stabilize nDer p 3 protein using specific serine protease inhibitors treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations